Diseño de un sistema semiautomático de apilamiento de cajas de cartón de producto terminado (2022)
The purpose of this project is the design of a semi-automatic cardboard box stacking system, which consists of 5 sections, the first being a conveyor belt that lifts the boxes, followed by a roller conveyor that positions the boxes, then a lateral pusher. that groups the boxes, then a pneumatic system which stacks the boxes on the last section, which is a rack-and-pinion elevator from which the stack of boxes with reinforced stowage can be removed; with which it seeks to improve the conditions that operators face daily when stacking the boxes in the industry, the project focuses on the prevention of accidents of the operators when carrying out their work and additionally contributes to the improvement in times of preparation keeping intact the integrity of the product at the time of packing.